(untitled) - Alexander, Charles K. (Boston, MA., 2007)
Alexander and Sadiku's third edition of Fundamentals of Electric Circuits continues in the spirit of its successful previous editions, with the objective of presenting circuit analysis in a manner that is clearer, more interesting, and easier to understand than the other texts in the market. Students are introduced to the sound, six-step problem solving methodology in chapter one, and are consistently made to apply and practice these steps in practice problems and homework problems throughout the text and online using the KCIDE for Circuits software.
Toán kỹ thuật
Keywords: Electric circuits